Effects of Vitamin D on the Histomorphology of Norethisterone-Induced Hepatosteatosis in Female Rats - Tabassum, Asima; Kiani, Muhammad Rizwan Bashir; Zahid, Aqsa; Rashid, Saadia; Umbreen, Faiza; Zakria, Irum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the histomorphological effects of Vitamin D on Norethisterone-induced hepatosteatosis in female rats.Study Design: Laboratory-based experimental study.Place and Duration of Study: Department of Anatomy, Army Medical College/National University of Medical Sciences Rawalpindi in collaboration with the National Institute of Health (NIH), Pathology Laboratory Pak Emirates Military hospital,and Armed Forces Institute of Pathology, (AFIP) Rawalpindi Pakistan, from Aug to Nov 2021.Methodology: Thirty female Sprague Dawley rats weighing 250-300 gm were randomly divided into three groups (10 for each group). Group-A served as control. For eight weeks, Group-B was given Norethisterone 4.55 mg/kg/day by oral gavage.Group-C was given 1000 IU/kg/day of Vitamin D by intraperitoneal injection for five consecutive days/week, along with Norethisterone for eight weeks. All the animals were sacrificed at the end of the experiment. The colour and consistency of the liver specimen were noted. Liver specimens were processed and staining was done with H & E stains. Histologically steatosis in the specimen was assessed.Results: The results were compared among the groups. Experimental Group-B, when compared with Control Group-A,showed a significant change in the colour (p-value 0.033) and consistency of the liver (p-value 0.033) along with marked steatosis (p-value 0.001). There was a significant improvement in hepatosteatosis (p-value 0.001), which led to improved colour (p-value 0.029) and consistency of the liver (p-value 0.029) in Experimental Group-C when compared with Experimental Group- B.Conclusion: Vitamin D ameliorates hepatosteatosis induced by Norethisterone in the female rat.